2017
DOI: 10.3126/hprospect.v16i2.18643
|View full text |Cite
|
Sign up to set email alerts
|

Risky work: Accidents among Nepalese migrant workers in Malaysia, Qatar and Saudi Arabia

Abstract: Background: Nepal is a growing supplier of migrant labour for factories in Malaysia and building sites in the Middle East. This study assessed the extent of workplace accidents among Nepalese migrant workers in Malaysia, Qatar and Saudi Arabia. Methododology:A questionnaire survey was conducted at Nepal's main international airport with men who returned from working in Malaysia, Qatar and Saudi Arabia. The questionnaire was completed by 403 migrant workers from these three countries. Where possible the questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…A total of 33 papers were included in the review among them 12 studies were conducted in Qatar, 12–23 8 in Malaysia, 24–31 9 in Nepal, 5 7 32–38 2 in Saudi Arabia, 39 40 1 each in UAE 41 and Kuwait, 42 respectively. Two study included all GCC countries and Malaysia, 7 38 another two study included Malaysia, Qatar and Saudi Arabia 32 33 and further two included in Qatar, Saudi Arabia and UAE 5 34 ( table 1 ). The study design varied across the studies; the review included 13 retrospective analysis of routine healthcare data 7 12–15 18 20 25 35 37 39 40 42 and 18 cross-sectional studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 33 papers were included in the review among them 12 studies were conducted in Qatar, 12–23 8 in Malaysia, 24–31 9 in Nepal, 5 7 32–38 2 in Saudi Arabia, 39 40 1 each in UAE 41 and Kuwait, 42 respectively. Two study included all GCC countries and Malaysia, 7 38 another two study included Malaysia, Qatar and Saudi Arabia 32 33 and further two included in Qatar, Saudi Arabia and UAE 5 34 ( table 1 ). The study design varied across the studies; the review included 13 retrospective analysis of routine healthcare data 7 12–15 18 20 25 35 37 39 40 42 and 18 cross-sectional studies.…”
Section: Resultsmentioning
confidence: 99%
“…Adhikary et al reported that around one-fifth (17%) of migrant workers had experienced work related accidents. 32 Poor working environment and not being registered with a doctor was associated with a greater perceived health risk at the work place. Another study reported that over a quarter (27.9%) of migrant workers had experienced occupational injuries: more than half (52%) of these workers fell from a height, 20% had injuries due to fall of a heavy object, 17% had motor vehicle accident injuries, 5% had machinery injuries and remaining 5% had other work related injuries.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sample size and Sampling procedure forty six (46) subjects formed an ideal sample size for the study, for a population running into forty six, the sample size should be 50%, the researcher therefore aimed at least for 50% subjects in each group as reflected in table (1). The registered contractors of infrastructures construction companies is categorized in groups from I to II according to capacity limited by the value of work in of millions of shillings, beginning from category I and II.…”
Section: Population and Samplementioning
confidence: 99%